Just Trolley: Implementation of industrial IoT and digital twin-enabled spatial-temporal traceability and visibility for finished goods logistics. (April 2022) - Wu, Wei; Zhao, Zhiheng; Shen, Leidi; Kong, Xiang T.R.; Guo, Daqiang; Zhong, Ray Y.; Huang, George Q.
Abstract: The efficiency of the factory logistics after production and before warehousing becomes no less important in terms of the overall productivity, product quality, and service level, especially under mass customization. However, it almost remains traditional in the industry and gains insufficient academic studies due to its triviality and irregularity. This paper aims to develop an Industrial Internet of Things (IIoT) and Digital Twin (DT) enabled platform of real-time tracking and tracing (ID-PORT) for finished goods logistics. The architecture facilitates collaborative tracking methods to actualize timely spatial-temporal traceability and visibility with cyber-physical synchronization. Furthermore, smart location-based services (LBS) are activated to enhance operational efficiency. A real-life case study is conducted in a world-leading computer manufacturer's factory to illustrate the feasibility and evaluate the performance of the platform. An implementation concept, "Just Trolley", which treats every location or area as a trolley in the digital world, is created as guidance to streamline the system development, deployment and operations. A comparative analysis shows a significant reduction in the time of product picking-up and order emergency detecting, further shortening the order lead time and improving the service level. Meanwhile, the overall productivity has also increased. The insights and lessons reaped from this case may spark new ideas and inspire practitioners to meet similar needs in the industry.